The Kinetics of Inhibition of the Action of Thrombin by the Fibrinopeptides Formed during the Clotting of Fibrinogen - Silver, A; Murray, M (Thrombosis and Haemostasis, 1966)
Various investigators have separated the coagulation products formed when fibrinogen is clotted with thrombin and identified fibrinopeptides A and B. Two other peaks are observed in the chromatogram of the products of coagulation, but these have mostly been dismissed by other workers. They have been identified by us as amino acids, smaller peptides and amorphous material (37). We have re-chromatographed these peaks and identified several amino acids. In a closed system of fibrinogen and thrombin, the only reaction products should be fibrin and peptide A and peptide B. This reasoning has come about because thrombin has been reported to be specific for the glycyl-arginyl peptide bond. It is suggested that thrombin also breaks other peptide linkages and the Peptide A and Peptide B are attacked by thrombin to yield proteolytic products. Thrombin is therefore probably not specific for the glycyl-arginyl bond but will react on other linkages as well.If the aforementioned is correct then the fibrinopeptides A and B would cause an inhibition with the coagulation mechanism itself. We have shown that an inhibition does occur. We suggest that there is an autoinhibition to the clotting mechanism that might be a control mechanism in the human body.The experiment was designed for coagulation to occur under controlled conditions of temperature and time. Purified reactants were used. We assembled an apparatus to record visually the speed of the initial reaction, the rate of the reaction, and the density of the final clot formed after a specific time.The figures we derived made available to us data whereby we could calculate and plot the information to show the mechanism and suggest that such an inhibition does exist and also further suggest that it might be competitive.In order to prove true competitive inhibition it is necessary to fulfill the criteria of the Lineweaver-Burk plot. This has been done. We have also satisfied other criteria of Dixon (29) and Bergman (31) that suggest true competitive inhibition.